The Direct Exposure of Cortisol Does Not Modulate the Expression of Immune-Related Genes on Tissue Explants of Mucosal Surfaces in Rainbow Trout (Oncorhynchus mykiss) Nor in Gilthead Sea Bream (Sparus aurata) - Vallejos-Vidal, Eva; Khansari, Ali Reza; Soliva-Dueso, Lluc; Balasch, Joan Carles; Tort, Lluis; Reyes-López, Felipe E. (Frontiers in Marine Science, 2022)
The stress response in fish is characterized by the activation of the HPI axis resulting in the release of cortisol. Previous studies in rainbow trout (Oncorhynchus mykiss) and gilthead sea bream (Sparus aurata) have shown that an acute stressor modulates the expression of immune- and stress-related genes in mucosal-associated lymphoid tissues (MALTs), particularly in the skin (SALT), gills (GIALT), and gut (GALT). However, there are no antecedents on whether the modulation on the mucosal transcriptomic profile is coordinated through the local presence of cortisol in the mucosal tissue surface. Thus, the aim of this study was to evaluate the effect of cortisol upon the modulation of a set of immune- (il-1β, il-6, tnf-α, and cox-2) and stress-related (hsp70, gr1) genes. For this purpose, tissue explants cultures were incubated with cortisol (100 ng/100 mg tissue) for 2-, 4-, and 24 h and the gene expression profile was evaluated at each time-point by real-time PCR. No differences were found in the gene expression between cortisol-incubated tissue explants and mock-incubated tissues in any of the time-points tested for both species. These results suggest that the quick modulation of the gene expression during the first 24 h after the exposure to stressor challenge reported in previous studies, is probably coordinated and mediated through a systemic-dependent mechanism but not through a peripheral/local response on mucosal tissue surfaces.